Pengaruh Kualitas Layanan, Citra Bank Dan Kepercayaan Nasabah Terhadap Kepuasaan Nasabah Di Pt. Bank Sinarmas Ende - Bie, Yosefa; Langga, Lambertus; Dua Mea, Maria Helena Carolinda (Program Studi Manajemen Universitas Flores, 2021)
The purpose of this study was to examine the effect of quality services, bank image and customer trust simultaneously and partially on customer satisfaction PT. Bank Sinarmas Branch Ende, independent variable in this study is the quality of service, bank image and trust costumer. While the dependent variable is customer satisfaction PT. Bank Sinarmas Ende Branch. In this study, the determination of the sample was carried out by the method non probability. The sample used was 94 people. Hypothesis testing with perform multiple linear regression analysis. Before testing the hypothesis reliability and validity test were carried out. The result is that all variables are valid and reliable, the results of the F test show Fcount > Ftable with a significant of 0,000. With the first hypothesis states “service quality,bank image and customer trust simultaneously has a significant effect on satisfaction customerof PT. Bank Sinarmas Branch Ende, can be supported by the truth. Results t test shows c=each variable with a significance less than 0,05. This the second hypothesis which states service quality, Bank image and customer trust partially have a significant effect to customer satisfaction of PT. Bank Sinarmas Branch Ende can be supported the truth